Studi Literatur: Aktivitas Imunomodulator Tanaman Jintan Hitam (Nigella sativa L.) - Tanti Dwi Gunawati; Febrina Mahmudah; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
An immunomodulator is a substance or agent that can cause immunomodulatory activity by changing or affecting the immune system or producing an unwanted immune response through dynamic regulation of the target immune system. Black cumin (Nigella sativa L.) or better known to the public with Habbatus saudah already included in the Ranunculaceae plant family has properties to treat various diseases such as strengthening the immune system, asthma, bronchitis, diabetes, anti-histamine, anti-oxidant, anti-tumor. digestive tract and bacteria. This study aims to analyze the literature related to the immunomodulatory activity of black cumin plants. The research method used is a literature study. Data searches were carried out using online search engine instruments such as Google Scholar, Pubmed, Science Direct, Elsevier, NCBI without any time limit for cited journals. The results of research from 10 journals that have been analyzed show that black cumin (Nigella sativa L.) has acted as an immunomodulator.